2014
DOI: 10.18632/oncotarget.2120
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of glucose turnover by 3-bromopyruvate counteracts pancreatic cancer stem cell features and sensitizes cells to gemcitabine

Abstract: According to the cancer stem cell (CSC) hypothesis, the aggressive growth and early metastasis of pancreatic ductal adenocarcinoma (PDA) is due to the activity of CSCs, which are not targeted by current therapies. Otto Warburg suggested that the growth of cancer cells is driven by a high glucose metabolism. Here, we investigated whether glycolysis inhibition targets CSCs and thus may enhance therapeutic efficacy. Four established and 3 primary PDA cell lines, non-malignant cells, and 3 patient-tumor-derived CS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 28 publications
2
49
0
Order By: Relevance
“…However, the role and significance of this propensity of CSCs toward highly glycolytic metabolism remain largely unknown. Recent studies have shown that 3-bromopyruvate, a hexokinase 2 (HK2) inhibitor, and its derivatives (pentyl 3-bromopyruvate ester [P-BrPE] and 3-bromo-2-oxopropionate-1-propyl ester [3-BrOP]) reduce the viability of CSCs and that knockdown of GLUT3 inhibits the growth of brain tumor CSCs [23, 25-28]. While all these studies do indicate that the glycolytic metabolism plays an essential role in the survival and proliferation of CSCs, it still remains to be shown whether the glycolytic metabolism has a role in the maintenance of the self-renewal capacity of CSCs.…”
Section: Discussionmentioning
confidence: 99%
“…However, the role and significance of this propensity of CSCs toward highly glycolytic metabolism remain largely unknown. Recent studies have shown that 3-bromopyruvate, a hexokinase 2 (HK2) inhibitor, and its derivatives (pentyl 3-bromopyruvate ester [P-BrPE] and 3-bromo-2-oxopropionate-1-propyl ester [3-BrOP]) reduce the viability of CSCs and that knockdown of GLUT3 inhibits the growth of brain tumor CSCs [23, 25-28]. While all these studies do indicate that the glycolytic metabolism plays an essential role in the survival and proliferation of CSCs, it still remains to be shown whether the glycolytic metabolism has a role in the maintenance of the self-renewal capacity of CSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Another hedgehog antagonist Vismodegib (GDC-0449), inhibits pancreatic CSC characteristics in vitro [81] . Using GDC-0449, a human phase I clinical trial is ongoing [82] , which preliminarily suggest that GDC-0449 has good safety profile and antitumor activity for some of the locally advanced or metastatic solid tumors. Pancreatic cancer progression was inhibited by sulforaphane, green tea catechins and quercetin by inducing let7a miRNA and inhibiting Kras and ALDH1 activity [82] .…”
Section: Signaling Pathways Altered By Cscsmentioning
confidence: 99%
“…Using GDC-0449, a human phase I clinical trial is ongoing [82] , which preliminarily suggest that GDC-0449 has good safety profile and antitumor activity for some of the locally advanced or metastatic solid tumors. Pancreatic cancer progression was inhibited by sulforaphane, green tea catechins and quercetin by inducing let7a miRNA and inhibiting Kras and ALDH1 activity [82] . The 3-Bromopyruvate, a glycolysis inhibitor blocked CSC signaling in PC cell lines and the spheroids derived from patients [83] .…”
Section: Signaling Pathways Altered By Cscsmentioning
confidence: 99%
“…In addition, protein phosphatase activity is associated with tumors. Fish oil suppressed cell growth of colorectal cancer by regulating PTEN and nuclear factor-κB signaling (9 (12) reported that ribonuclease inhibitor suppresses proliferation and metastasis in colorectal cancer cells by inhibiting the PI3K/Akt signaling pathway. Catalpol is one of the primary active ingredients in rehmannia, which functions as a diuretic and laxative, and exhibits blood sugar-lowering, liver protective, anti-aging and anticancer effects (13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%